The biopetrol synthesis from palmitic acid-heterogenous catalytic cracking with zeolite catalyst - Azrul Ariff, Abdul Halim @ Abdullah (2010)
Biofuel is defined as fuel produced from derivation of vegetable oils and specifically, biopetrol is defined as fuel which has the same characteristic with the petrol, but is produced from palmitic acid that is dominated in palm oil where the conversion of palmitic acid is done to get the molecular formula and structure of isooctane. Due to depletion of fossil fuel, environmental issues, and rising of petrol price, biopetrol can be the alternative fuel to the fossil fuel. Catalytic cracking method is conducted in this research due to the low yields from thermal cracking method. Futhermore, Malaysia is plenty with palm oil which palmitic acid is dominated in palm oil composition. In recent years, there have been several other studies on the production of hydrocarbons from palm oil mainly bio-gasoline (biopetrol) which have been carried out using cracking catalysts. Zeolites have shown excellent performance as solid acid cracking catalysts due to their higher selectivity. Many researchers have studied that dynamic catalytic cracking method will produce much higher yields than static cracking method and thermal catalytic cracking method. Through catalytic cracking process, palmitic acid is catalytic crack with 5g zeolite and 4 different rotation speed which is 600rpm, 780rpm, 960rpm and 1140rpm. The distillated product is diluted with mixture solution hexane at the ratio of 1:24. All the product samples are analyzed with Gas Chromatographer (GC). The isooctane concentrations are increased when the speed of reaction are increased, but not obviously. The lowest percentage concentration of isooctane obtained is 16.63376% and the highest percentage concentration of isooctane obtained is 23.09627%. These yields are much higher than the yields produced from static cracking method which is 20.7210% to 23.09627 %. It showed that the dynamic catalytic cracking method will produce much higher yields for biopetrol synthesized compared to thermal cracking method.